Prevalence of pre hypertension and its association to risk factors for cardiovascular diseases among male undergraduate students in Chennai - Logaraj, M.; Madhavan, R. S. Dinesh; Balaji, R. (International Journal Of Community Medicine And Public Health, 2017)
Background: Recent studies have documented an increase in the risk of cardiovascular diseases (CVD) and a high rate of progression to hypertension in persons with pre hypertension. Methods:A cross-sectional study was conducted among students of a university situated in the suburban area of Chennai with an objective to estimate the prevalence of pre-hypertension among male students and to assess the association between pre hypertension and risk factors for cardiovascular diseases. Among 403 students studied which included 200 medical and 203 engineering students with the help of pre tested structured questionnaire and measurements of height, weight, blood pressure; and postprandial blood glucose were carried out as per standard procedure. Results: About 30.3% of the students consume alcohol. The prevalence of pre hypertension and hypertension was 49.6% and 19.1% among male students. The prevalence of pre-hypertension was higher in medical students (51.5%) compared to engineering students (47.8%). Higher risk of being pre hypertensive were noted above the age of 20 years (OR= 4.32), fruit intake less than 3 days a week (OR= 1.03), smokers (OR= 1.13), alcohol intake (OR= 1.56), lack of physical exercise (OR=1.90), BMI of more than 25 kg/m2 (OR=1.99). But statistically significant difference was noted between pre hypertensive and normotensive for age (p<0.0001), lack of physical exercise (p=0.004) and BMI (p=0.015). Conclusions:In conclusion higher prevalence of smoking, alcohol intake, lack of physical exercise, overweight and increased waist circumference and postprandial blood sugar more than 140 mg/dl was noted among pre-hypertensive compared to normotensive.